Konstruksi Pemberitaan Tentang Program Kampanye Capres-Cawapres WIN-HT - Yohanes Nandus (Universitas Mercu Buana, 2019)
The development of technology and the Internet in today's world of social media spur construction developments that led to the development of the mass media very fast rate so that there are some changes in it becomes a challenge for the world community communication. This mass media became a tool for political communication politicians. As part of the political situation, the program is very interesting political campaigns from the perspective of the news. Then okezone.com is one of the online media that aggressively cover it. Coverage program WIN-HT campaign shows how the interests and values are displayed. interest emergence and value on the news carried by framing (framing). Campaign program WIN-HT in the news okezone.com as a form of representation. This study aims to determine the representation of interests in the media okezone.com. To find the interest, and the value of the construct news program vice presidential campaign WIN-HT, researchers used a method of analysis framing Zhondang Pan and Kosicki in uncovering the hidden purpose of news that syntax, script, thematic, and rhetorical. With four of the framing device okezone.com interest representation in the media in question can be known. The theory used in this research is the theory on Berger and Luckman construction and sociological theory of Pamela J. Shoemaker and SDReese. Research results indicate that the presence of construction proclamation of 2014 vice presidential campaign program WIN-HT from Hanura party. Okezone.com very clearly good news sorting of syntactic structure, script, thematic, and rhetorical. Thus Legal alignments against Hanura party very prominent. In the news okezone.com, interest representation of popular programs to many people. Keywords: Construction of social, media, Framing Analysis.